Implementation of Free Learning Curriculum at The Inclusive School at The Senior High School of Human Bekasi - Mamah; Suharyat, Yayat; Aprillilantoni (Proceeding International Conference on Education, 2023)
The curriculum is the heart of education. The curriculum is dynamic and follows the changing times. This study aims to analyze the implementation of the Merdeka Learning Curriculum, evaluate its impact on student learning, and identify the implications of this implementation at the Senior High School of Human Bekasi. Data collection techniques include class observations, interviews with teachers and students, and analysis of curriculum documents. Data analysis was carried out using a written qualitative approach. Data from observations, interviews, and document analysis were reviewed thematically to identify patterns of implementation, changes in student learning, and teachers' understanding of these approaches. The results showed that implementing the Independent Learning Curriculum had a good impact on student learning. Flexibility, independence, and active participation of students in learning increases. Teachers also reported positive changes in student engagement and achievement of learning objectives. This research implies the need for adequate support and training for teachers in implementing the Free Learning Curriculum. Educational institutions must also create an environment that supports creativity, innovation and student involvement in learning.